2021
DOI: 10.1101/2021.11.25.21266850
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A slow road from meat dominance to more sustainable diets: an analysis of purchase preferences

Abstract: BackgroundAchieving a sustainable and healthy diet requires increased replacement of red meat with more sustainable foods. There is a call for novel methodologies to assess the potential of different interventions and policies in enhancing the transition from the current to more sustainable choices.ObjectiveWe aimed to characterize consumer clusters with similar preferences in protein sources, to compare the purchase prices of these foods, and to identify ongoing transitions from one protein source to another.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
(54 reference statements)
0
1
0
1
Order By: Relevance
“…Osa havaitsemistamme eroista voi selittyä ruoan hinnalla (12). Tyypillisesti energiatiheät, mutta muuten ravintotiheydeltään heikommat ruoat ovat edullisia, kun taas esimerkiksi kala (42,43), hedelmät ja kasvikset kuuluvat kalliimpiin ruokaryhmiin (43). Suomalaisperheillä epäterveellisten elintarvikkeiden osuus ostosten kokonaishinnasta on todettu olevan suurinta alimmissa tuloluokissa (14).…”
Section: Pohdintaunclassified
“…Osa havaitsemistamme eroista voi selittyä ruoan hinnalla (12). Tyypillisesti energiatiheät, mutta muuten ravintotiheydeltään heikommat ruoat ovat edullisia, kun taas esimerkiksi kala (42,43), hedelmät ja kasvikset kuuluvat kalliimpiin ruokaryhmiin (43). Suomalaisperheillä epäterveellisten elintarvikkeiden osuus ostosten kokonaishinnasta on todettu olevan suurinta alimmissa tuloluokissa (14).…”
Section: Pohdintaunclassified
“…On the other hand, the prices of legumes and grains, considered both healthy and climatefriendly, can be substantially less expensive per kJ than meat (15) . Our previous study showed that plant-based protein sources were bought, on average, for a cheaper price than meat (16) . In addition, in a US study, vegetarians spent less money on food purchases than meat eaters (17) .…”
Section: Introductionmentioning
confidence: 99%